Upaya Meningkatkan Aktifitas dan Hasil Belajar Kimia Pokok Bahasan “Tata Nama Senyawa Kimia“ Melalui Model Pembelajaran Demonstrasi dengan Alat Peraga Kartu Tata Nama Senyawa - Berliana Y Pasaribu (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
The purpose of this classroom action research was to determine the increase outcome because of using chemical compounds system cards methods. This method was used on the 35 X-C Class students in SMAN 3 South Jakarta. This research included a description of the research carried out by two cycles where every single cycle consists of 3 times meeting hour and each cycle consisting of planning,, observation and reflection with action approach research. The results of description analysis revealed, with the following data:First cycle, average achievement of chemical material chemical nomenclature is 73. 14, the percentage of completeness 42%, and the second cycle, the average results of studying chemistry has increased to 81 with a percentage of 90%, the percentage of active learners in the classroom are:First cycle average percentage of active learners from 58. 82% to 82. 56% in the second cycle. Thus, it can be concluded that the results of the chemical study of the nomenclature of chemicalcompounds can be enhanced by using chemical system cards method on 3 Senior High School XC Class 3 student atthe South Jakarta Setiabudi II.